Stres Kerja Wartawan Ditinjau dari Kepribadian Tahan Banting dan Masa Kerja - Ilham R. Saputro; Abdurrohim Abdurrohim; Erni Agustina Setiowati (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2014)
The purpose ofthis study was to examine the correlation between hardiness personality and work period to work stress. The hypotheses is that hardiness and work period have negative impact to work stress. The participants in this study are 90 journalists at Central Java. Quota stratified sampling methods was used in the study. Data were collected with work stress and hardiness scale. Regression analysis technique used to test the major hypotheses and minor hypotheses tested with partial correlation analysis. The result showed that there are significant correlation between hardiness and work period to workstress with R = 0.265 and F - 3.272, p = 0.043 (p <0.05). Hardiness has a negative correlation to work stress with ryw = -0,262, p = 0.013 (p <0.05). However, the correlation between work period and work stress was not significant with ry^, = 0.092, p = 0.839 (p> 0.05) as showed by its comparison test with oneway anova with F = 0.629 andp = 0.535(p = <0.05). Keywords:hardiness, workperiod, workstress.